Effects Of Creation Deed of Sale and Purchase of Land Which Does Not Match Procedure of Making Land Deeds - Fery Harjanto; Defry Dwi Irmawan; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Land registration is held to ensure legal certainty. The absence of legal certainty in land ownership rights will lead to the deed of sale of land that is unlawful, because it is made without going through the procedures of land deed that has been determined. The purpose of this study was to analyze the causes of the Deed of Sale and Purchase of Land that is not in accordance with the procedures of the Land Deed-making event and to analyze the legal consequences Deed of Sale and Purchase of Land that is not in accordance with the procedure of making the show. This study using sociological juridical approach with analytic descriptive data analysis techniques. Data collection was done by using the study of literature. The results showed that the factors causing the deed of sale of land that does not follow the procedure of deed of land caused by the confidence that is too high between the parties with PPAT, too many employment PPAT so the time to investigate is limited, lack of understanding PPAT to the provisions of the law, the value of the transaction so that PPAT follow the will of the parties, relationships and friendship factor. Based on data analysis concluded the legal consequences of land purchase deed which is not in accordance with the procedures of a deed is PPAT be dishonorably discharged, the deed of sale published degraded proof strength be deed under the hand and third parties can use this for their own interests.Keywords: Deed of Sale and Purchase of Land; Procedure for the Deed; Effects.